Machine Learning Model Uses Pain Sketches to Predict Headache Sur- gery Outcomes: a literature review - Filho, Helvécio Neves Feitosa; Lima, Rayndrick Kelryn Assis; Lima, Raynrich Kevin Assis; Santos, Isabela Cacau Sousa; Appio, Pedro Roa; Lima, Eduarda Maia; Macêdo, Carolina Helen Soares De; Furtado, Nithyananda Araújo; Carate, Caio Kacem (Headache Medicine, 2023)
Full abstract in PDF.